(untitled) (Research, Society and Development, 2021)
Oral cancer is a chronic degenerative disease that can lead to death. Among the risk factors is ultraviolet radiation resulting from sun exposure. People who develop labor activities in external environments, such as field workers in the rural settlement Sítio Aracaju, in the municipality of Iguatu, state of Ceará, are part of the risk group for tumor development. The main objective of the research was to investigate the perception of rural workers about the educational practice in health on the oral cancer theme. This was an action research with a qualitative approach, data collection through a form, unsystematic direct observation and interviews. The educational practice was elaborated based on the presuppositions of integral human formation and health promotion; the first is constituted as the basis of professional and technical education (PTE), while the second focused on autonomy, and the political and social co-responsibility of the subjects involved. The educational practice consisted of a sociocultural approach based on Paulo Freire’s popular education and on the pedagogy of the problematization of Juan Díaz Bordenave, using the conversation wheel that was consolidated by Maguerez’s arch. The experience resulted in an extension project with a potential application in several other social realities.